Hubungan antara, Self Esteem dengan Self Disclosure pada Saat Chatting di Facebook: The relationship between Self Esteem and Self Disclosure when Chatting on Facebook - Santi, Novi Nitya; Damariswara, Rian (Universitas Muhammadiyah Sidoarjo, 2017)
Facebook is an internet based social media that were populer at the moment. The use of sosial media is very populer no exception student. Students communicatem confide and seek information through facebook. Of the activities, appears a phenomenon experienced by students of the symptoms of self esteem and self disclosure. This research aims to determine the relationship between self esteem and self disclosure. The relationship between the level of self esteem with self disclosure while chatting on facebook worth 0,766. Meaning that the reletionship between the level of self esteem with self disclosure is very strong and direct. Where a person who has high self esteem will be able to able to demonstrate self-disclosure are effective in communicating that is: be open, able to empathize, to be positive in the communication process and feel similar to the communication partner. Conversely a low self esteem are less able to express himself well, fear of failure in social relations